From Cashless Transaction Capability to MSME Creditworthiness: The Role of Digital Accounting Quality in Indonesia’s Fintech Lending Ecosystem - Duni Duni; Arniwita Arniwita; Muhammad Fithrayudi Triatmaja; Dika Anggara Putra; Willy Nurhayadi; Eko Sudarmanto (Eastasouth Institute, 2026)
The increasing adoption of cashless payment systems has created new opportunities for Micro, Small, and Medium Enterprises (MSMEs) to improve financial transparency and access fintech-based financing. This study examines the influence of cashless transaction capabilities on MSME creditworthiness, with digital accounting quality serving as a mediating variable in Indonesia’s fintech lending ecosystem. A quantitative research design was employed using data collected from 150 MSME owners and financial managers who actively used digital payment services and had experience with fintech-based financial services. The research variables were measured using a five-point Likert scale, and the data were analyzed using Structural Equation Modeling–Partial Least Squares with SmartPLS 3. The results show that cashless transaction capabilities have a significant positive effect on digital accounting quality and MSME creditworthiness. Digital accounting quality also has a significant positive effect on MSME creditworthiness. Furthermore, digital accounting quality significantly mediates the relationship between cashless transaction capabilities and MSME creditworthiness, indicating partial mediation. The model explains 68.7% of the variance in MSME creditworthiness and demonstrates satisfactory predictive relevance and model fit. These findings indicate that cashless transaction capabilities improve creditworthiness not only through traceable transaction histories but also by enhancing the accuracy, completeness, timeliness, and reliability of digital accounting information.